Office jobs from the 1980s to the present day : a case example of a mixed-methods approach - Blank, Marco [Verfasser]; Ehmann, Kathrin [Verfasser]; Baum, Myriam [Verfasser]; Tiemann, Michael [Verfasser] (My University, 2020)
"Labour research in Germany overlooks office jobs as a research subject, despite the fact that office employees were among the first to be directly confronted with technological change and whose tasks could be replaced by algorithms. Devising a mixed-methods research (MMR) agenda to investigate the ways office employees deal with ongoing processes of automation and digitization of their workplaces and companies' changing requirements from the 1980s to today, we provide a case example of a specific and complex MMR design. In parallel, we offer a new, resource-oriented perspective on office employees. This may help foster resilience in a considerably large group of employees in Germany and elsewhere. Office jobs are identified by their 3-digit code in the German Classification of Occupations (KldB) of 2010. Our MMR approach requires conscious triangulation of various qualitative (employee and expert interviews) and quantitative data sources (micro-level: Employment Surveys from 1979–2019 and the Microcensus; meso-level: Training Panel, continuous training monitor and job advertisements; macro-level: qualification and occupational field projections). Further, complementarity benefits arise from considering quantitative (secondary) data together with qualitative primary data. Reflecting the data against the research subject via multiple interviews helps provide a deeper understanding of processes of change in office jobs. Addressing advantages and challenges of changing survey instruments and classifications over time, the research teams' different backgrounds, and restrictions due to the corona pandemic, we seek to provide a substantial (case) example for others entering the MMR terrain." (Authors' abstract ; BIBB-Doku)
Keywords: S 6.4.3.5 Bürofach-, Bürohilfskräfte; G 1.2.3 Qualifikationsentwicklungen; Büroberuf; Berufswandel; Digitalisierung; Mixed-Method